Electronic, and thermoelectric properties of half-heusler compounds MCoSb (M = Ti, Zr, Hf): a first principles study. (20th March 2019) - Joshi, H; Rai, D P; Laref, Amel; Thapa, R K
Abstract: Full Potential Linearized Augmented Plane Wave method (FP-LAPW) method based on the Density Functional Theory (DFT) in combination with Boltzmann semi-classical transport equation (BTE) have been used to investigate the electronic, and thermoelectric properties of MCoSb type half-Heusler compounds. A most effective exchange potential developed by Tran and Blaha by modifying Becke-Johnson exchange potential called TB_mBJ potential has also been used to open the degenerated band gaps. The calculated results were compared with the available theoretical and experimental data. On careful observation of the band structure one can predict that MCoSb is a narrow indirect band gap semiconductor with electron transition along Γ- X symmetry point in the first Brillouin zone. The vibrational and thermodynamic properties were also studied form the quasi-harmonic approximations to confirm their mechanical and thermodynamical stability. Furthermore, the lattice thermal conductivity ( k l ) has been calculated from the Slack's equation. The low value of k l is highly promising for applications in the thermoelectric devices. The electronic part of thermoelectric parameters are calculated from Boltzmann semi-classical transport equation (BTE). However, they are associated with the relaxation time ( τ ) and decoupling τ is challenging. Therefore, we have calculated τ as a function of temperature by using the Bardeen and Shockley's deformation potential theory. The calculated ZT value is highest in case of TiCoSb at 800 K. The order of ZT values in MCoSb at a temperature range from 600–900 K is TiCoSb > ZrCoSb > HfCoSb. The carrier concentration has been optimized such as to give the maximum thermoelectric performance.